Optimal location for fibular osteotomy to provide maximal compression to the tibia in the management of delayed union and hypertrophic non-union of the tibia. Issue 4 (April 2022) - Lim, Anthony; Biosse-Duplan, Garance; Gregory, Alastair; Mahbubani, Krishnaa T; Riche, Fergus; Brassett, Cecilia; Scott, John
Highlights: Fibular osteotomies increase load in tibial fractures and are used to promote/enhance healing in cases of delayed or hypertrophic non-union. A novel protocol using a rig was designed to ascertain the ideal location for a fibular osteotomy, and explained by a beam model. An osteotomy proximal to the fracture site produces most tibial fracture loading. Abstract: Background: Tibial shaft fractures are the commonest long bone fracture, with early weight-bearing improving the rate of bony union. However, an intact fibula can act as a strut that splints the tibial segments and holds them apart. A fibular osteotomy, in which a 2.5 cm length of fibula is removed, has been used to treat delayed and hypertrophic non-union by increasing axial tibial loading. However, there is no consensus on the optimal site for the partial fibulectomy. Methods: Nine leg specimens were obtained from formalin-embalmed cadavers. Transverse mid-shaft tibial fractures were created using an oscillating saw. A rig was designed to compress the legs with an adjustable axial load and measure the force within the fracture site in order to ascertain load transmission through the tibia over a range of weights. After 2.5cm-long fibulectomies were performed at one of three levels on each specimen, load transmission through the tibia was re-assessed. A beam structure model of the intact leg was designed to explain the findings. Results: With an intact fibula, mean tibial loading at 34 kg was 15.52 ± 3.26 kg, increasing to 17.42 ± 4.13 kg after fibular osteotomy. This increase was only significant where the osteotomy was performed proximal to or at the level of the tibial fracture. Modelling midshaft tibial loading using the Euler-Bernoulli beam theory showed that 80.5% of the original force was transmitted through the tibia with an intact fibula, rising to 81.1% after a distal fibulectomy, and 100% with a proximal fibulectomy. Conclusion: This study describes a novel method of measuring axial tibial forces. We demonstrated that a fibular osteotomy increases axial tibial loading regardless of location, with the greatest increase after proximal fibular osteotomy. A contributing factor for this can be explained by a simple beam model. We therefore recommend a proximal fibular osteotomy when it is performed in the treatment of delayed and non-union of tibial midshaft fractures.